The tradeoff of solitude? Restoration and relatedness across shades of solitude - Ross, Morgan Quinn; Campbell, Scott W. (PLOS ONE, 2024)
Social interaction and solitude entail tradeoffs. Communicate Bond Belong (CBB) theory holds that social interaction can foster relatedness with others at the cost of social energy, whereas solitude can restore social energy at the cost of relatedness. The current study empirically tests this tradeoff of solitude and its implications for well-being by investigating different degrees of solitude. Less complete degrees of solitude (e.g., no interaction with others) were associated with more relatedness and restoration than more complete degrees of solitude (e.g., no interaction, no potential for it, and no engagement with media), speaking against a tradeoff. Solitude was less detrimental for well-being among individuals who perceived it to be associated with higher restoration and relatedness. Yet, this finding was independent of social energy expenditure, challenging CBB theory. Future work should consider motivations for solitude and longitudinal approaches.